Molecular Evidence Points to Strong Resemblance in the Parasitoid Species of Rice and Cogongrass Gall Midges, Platygaster spp. (Hymenoptera: Platygasteridae) - Hidayat, Purnama; Lestari, Yuliana Ayu; Nurulita, Sari (HAYATI Journal of Biosciences, 2025)
The rice gall midge, Orseolia oryzae, and the cogongrass gall midge, O. javanica, cause gall formation on rice and cogongrass (alang-alang) (Imperata cylindrica). Two different species parasitize these two gall midges but closely related platygasterids, Platygaster oryzae on the rice gall midge and P. orseoliae on the cogongrass gall midge. Both the gall midges and their parasitoids are often found in the adjacent area, raising a question about the relationship between the two gall midges and their parasitoids. This research aims to study the molecular identity of the rice and cogongrass gall midges, along with their platygasterid parasitoids, based on partial sequences of the mtCOI gene. Samples were collected from rice and cogongrass in the adjacent area in Cianjur, West Java Province, and a rice field with no cogongrass in Bogor, West Java Province. Successful DNA amplification was achieved using universal primers for mtCOI. Nucleotide sequencing analysis revealed that the rice gall from Bogor and Cianjur shared 100% similarity and 93.2-99.3% similarity with the rice gall from other countries. Notably, the parasitoids P. oryzae collected from rice in Bogor and Cianjur shared 97.2% similarity with P. orseoliae collected from cogongrass in Cianjur. These findings suggest that the platygaster parasitoids associated with the rice gall and the cogongrass gall midges are identical, serving as potential natural enemies for both pests. This study represents the first molecular identification report of rice and cogongrass gall midges and their platygasterid parasitoids from Java Island, Indonesia.